The Effect of Disulfiram and Copper on Cellular Viability, ER Stress and ALDH Expression of Human Meningioma Cells - Ying Kao; Li-Chun Huang; Shao-Yuan Hsu; Shih-Ming Huang; Dueng-Yuan Hueng (Biomedicines, 2022)
(1) Background: Meningiomas are the most common intracranial tumors in adults; currently there is no effective chemotherapy for malignant meningiomas. The effect of disulfiram (DSF)/Copper (Cu) on meningiomas remains unclear; (2) Methods: The impact of DSF/Cu on cell viability of meningioma adhesion cells (MgACs) and sphere cells (MgSCs) was assessed via MTS assay. The effects of DSF/Cu on intracellular Cu levels, cell senescence, and apoptosis were analyzed using CopperGreen, C12FDG, and Annexin V assays. Intracellular ALDH isoform expression and canonical pathway expression after DSF/Cu treatment were analyzed using mRNA microarray and Ingenuity Pathway Analysis, with further verification through qRT-PCR and immunoblotting; (3) Results: The viability of MgACs and MgSCs were inhibited by DSF/Cu. DSF/Cu increased intracellular Cu levels and cellular senescence. DSF/Cu also induced ER stress in MgACs and activated the PERK/eIF2 pathway for further adaptive response, apoptosis, and autophagy. Finally, DSF/Cu inhibited the expression of different ALDH isoforms in MgACs and MgSCs; (4) Conclusions: DSF/Cu exerts cytotoxic effects against both meningioma cells and stem-like cells and has treatment potential for meningioma.